A Location-Based Management System for Enterprise Wireless LANs - Chandra, Ranveer; Padhye, Jitendra; Wolman, Alec; Zill, Brian; Padhye, Jitu (2007)
The physical locations of clients and APs in a wireless LAN may have a large impact on network performance. However, today's WLAN management tools do not provide information about the location of clients apart from which AP they associate with. In this paper, we describe a scalable and easy-to-deploy WLAN management system that includes a self-configuring location estimation engine. Our system has been in operation on one floor of our building for several months. Using our system to observe WLAN usage in our building, we show that information about client locations is crucial for understanding WLAN performance. Although WLAN location systems are a widely studied topic, the novel aspects of our location system primarily relate to ease of deployment. The main contribution of this paper is to show the utility of office-granularity location in performing wireless management tasks.